2020
DOI: 10.1016/j.jhydrol.2019.124393
|View full text |Cite
|
Sign up to set email alerts
|

Impact of layered heterogeneity on transient saltwater upconing in coastal aquifers

Abstract: This research investigated the effect of layered heterogeneity on transient saltwater upconing in a laboratory-scale coastal aquifer. The experiments were conducted in a 2Dlaboratory flow tank, and the response of the saltwater wedge to pumping was analysed in a heterogeneous aquifer system, where a low permeability layer was constructed in the middle of the aquifer. The SEAWAT code was used for validation and to perform additional simulations to explore the sensitivity of the critical pumping rate and the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Liu et al (2014) and Guo et al (2019) studied SWI in tidally affected stratified aquifers, similarly Dalai et al (2020) quantified the impact of shore slope, while Vithanage et al (2012) investigated aquifer salinization due to a tsunami‐like event. Similarly, Mehdizadeh et al (2014), studied saltwater ‐ freshwater interface on confined aquifers with impermeable strata, Abdoulhalik and Ahmed (2017a, 2017b) evaluated the suitability of various coastal protection techniques in layered hydrological systems, while Abdoulhalik et al (2020), investigated the impact of freshwater abstraction in heterogeneous coastal aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2014) and Guo et al (2019) studied SWI in tidally affected stratified aquifers, similarly Dalai et al (2020) quantified the impact of shore slope, while Vithanage et al (2012) investigated aquifer salinization due to a tsunami‐like event. Similarly, Mehdizadeh et al (2014), studied saltwater ‐ freshwater interface on confined aquifers with impermeable strata, Abdoulhalik and Ahmed (2017a, 2017b) evaluated the suitability of various coastal protection techniques in layered hydrological systems, while Abdoulhalik et al (2020), investigated the impact of freshwater abstraction in heterogeneous coastal aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial discretisation and dispersivity values satisfied the grid Peclet number criterion. The molecular diffusion was neglected in this work, following other studies e.g., [9,10,13,20,21]. A constant head was set at the coastal boundary (C = 36.16 g/L), and a variable head was set at the inland freshwater boundary (C = 0 g/L).…”
Section: Methodsmentioning
confidence: 99%
“…Abdelgawad et al [9] found the critical pumping rate of a well, the rate at which 1% salt concentration reaches the well, was more sensitive to the well location than the well depth. Abdoulhalik et al [10] extended their study by analysing the critical pumping rate in layered heterogeneous coastal aquifers. They evidenced that critical pumping rate significantly decreased with decreasing hydraulic conductivity and thickness of the middle layer of the aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…Stoeckl et al [55] utilized laboratory testing to introduce the novel concept of post-pumping saline intrusion, which is the phenomenon of seawater intruding further inland than the location of a well after pumping has ceased. While all these studies assumed homogenous aquifer structures, Abdoulhalik et al [56] performed the only experimental study investigating pumping well salinization in heterogeneous-stratified coastal aquifers. Since the hydrodynamics of fractured porous media vary significantly from those of granular aquifers, the fundamental mechanisms of pumping-induced saline intrusion in fractured aquifers are far from understood.…”
Section: Introductionmentioning
confidence: 99%